Performance of flood defences in the Netherlands during the 2021 Summer floods - Koelewijn, André; Pol, Joost; van Schaijk, Malou (Journal of Coastal and Riverine Flood Risk, 2023)
During the July 2021 Flood, the main flood defences along the River Meuse in the Netherlands performed well and did not breach. This paper provides an overview and description of the reported incidents related to flood defences, including a few breaches in minor flood defences. The incidents include overflow of embankments, sand boils, internal erosion at structures, and damage to a large weir and an outflow structure. Also, two local flood defences breached: an emergency embankment at Horn and an embankment in Roermond. During the event, the media reported on a dike breach at Meerssen/Bunde, however, after further investigation, it appeared that the concentrated outflow there was fuelled from a forgotten buried culvert.